Efficient Second Harmonic Generation by Mode Phase Matching in a Silicon Waveguide - Jiangchuan Huang; Hailong Han; Ang Liu; Hongfei Wang; Xiaoping Liu; Yi Zou; Minghui Lu; Yanfeng Chen (IEEE Photonics Journal)
Bulk silicon possesses no second-order susceptibility (χ(2)), inhibiting second-order nonlinear processes in the emerging silicon photonic platform. Here, we propose a method to overcome this limitation by enabling a third-order (χ(3)) nonlinear mixing scheme between optical waves and an externally applied static electric field inside a silicon waveguide. We show in theory that facilitated by a modal phase-matching scheme efficient second-harmonic generation can be realized under an applied voltage of 65 V, giving rise to an equivalent χ(2) = 4.7 pm/V. We also show that unlike the classical second-harmonic generation, the wavelengths of phase-matched pump and second-harmonic waves are pump-power dependent due to the χ (3) nature of this process.